The Biology and Targeting of FLT3 in Pediatric Leukemia - Annesley, Colleen E.; Brown, Patrick (Frontiers in Oncology, 2014)
Despite remarkable improvement in treatment outcomes in pediatric leukemia over the past several decades, the prognosis for high risk groups of acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL), as well as for relapsed leukemia, remains poor. Intensified chemotherapy regimens have somewhat improved success rates, but at the cost of drastically increased morbidity and long term adverse effects. With the success of imatinib in Philadelphia-chromosome positive leukemia and all-trans retinoic acid in acute promyelocytic leukemia, the quest to find additional molecularly targeted therapies has generated much excitement over the past 15 years. Another such possible target in pediatric acute leukemia is FMS-like tyrosine kinase 3 (FLT3). FLT3 aberrations are among the most frequently identified transforming events in AML, and have significant clinical implications in both high risk pediatric AML and in certain high risk groups of pediatric ALL. Therefore, the successful targeting of FLT3 has tremendous potential to improve outcomes in these subsets of patients. This article will give an overview of the molecular function and signaling of the FLT3 receptor, as well as its pathogenic role in leukemia. We review the discovery of targeting FLT3, discuss currently available FLT3 inhibitors in pediatric leukemia and results of clinical trials to date, and finally, consider the future promise and challenges of FLT3 inhibitor therapy.